The Role of Insulin Resistance and Thyroid Dysfunction in the Pathophysiology of Menstrual Cycle Disorders - Karimova , Mukima; Khabibullaeva , Noila (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This study investigates the synergistic impact of insulin resistance (IR) and thyroid dysfunction on the development of menstrual irregularities in reproductive-aged women. Menstrual cycle disorders represent a significant clinical challenge, often serving as early indicators of underlying metabolic and endocrine imbalances. The research focused on evaluating the correlation between Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) values and serum levels of Thyroid Stimulating Hormone (TSH) in 120 patients presenting with oligomenorrhea and amenorrhea. Methods involved a comprehensive clinical assessment, biochemical screening, and hormonal profiling. Results indicated a statistically significant prevalence of subclinical hypothyroidism among patients with elevated HOMA-IR scores ($3.8 ± 0.4$ vs $1.9 ± 0.2$ in the control group, $p < 0.05$). The findings suggest that IR exacerbates thyroid-mediated disruptions of the hypothalamic-pituitary-ovarian axis, leading to chronic anovulation. Conclusion: Integrated screening for both metabolic and thyroid parameters is essential for the effective management of menstrual health, as mono-therapy often fails to restore cyclic stability when dual pathways of dysfunction coexist.